2003
DOI: 10.1079/bjn2002747
|View full text |Cite
|
Sign up to set email alerts
|

Serum fatty acid levels, dietary style and coronary heart disease in three neighbouring areas in Japan: the Kumihama study

Abstract: CHD mortality is extremely low in Japan, particularly in rural districts, when compared with that in Western countries. This has been partly attributed to the difference in dietary lifestyle. We investigated the factors influencing CHD mortality in a rural coastal district of Japan, comprising mercantile, farming, and fishing areas with distinct dietary habits. We prospectively examined the incidence of CHD from 1994 to 1998, as well as coronary risk factors and serum fatty acid concentrations. The incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 35 publications
(34 reference statements)
6
35
1
1
Order By: Relevance
“…Serum levels of PUFAs are known to be differently distributed according to sex and age, reflecting dietary habits and age-related changes, and residential areas with different levels of fish consumption, [22][23][24][25][26] but their tendencies in STEMI patients remain unclear. In our study, the ratios of serum EPA/AA and DHA/AA in STEMI patients significantly varied in the male patients according to the age groups and were lower in younger men, as is the case for healthy people.…”
Section: Discussionmentioning
confidence: 99%
“…Serum levels of PUFAs are known to be differently distributed according to sex and age, reflecting dietary habits and age-related changes, and residential areas with different levels of fish consumption, [22][23][24][25][26] but their tendencies in STEMI patients remain unclear. In our study, the ratios of serum EPA/AA and DHA/AA in STEMI patients significantly varied in the male patients according to the age groups and were lower in younger men, as is the case for healthy people.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that n-3 PUFAs, including EPA and docosahexaenoic acid (DHA), exert antiplatelet and anti-inflammatory actions, in part through antagonizing the activity of proinflammatory eicosanoids derived from arachidonic acid (AA), one of the n-6 PUFAs 5,11) . Previous epidemiological studies reported that high n-3/n-6 PUFA levels and the EPA/ AA ratio are associated with a low rate of ischemic heart disease 12,13) . In addition, a sub-analysis of the JELIS and other studies suggested that a high serum EPA/AA ratio is significantly associated with a low incidence of cardiac death or myocardial infarction, and a low coronary plaque score 14,15) .…”
Section: Study Protocolmentioning
confidence: 99%
“…Recent reports have determined that unsaturated fatty acids can improve CAD. [3][4][5] Therefore, we hypothesized that fatty acids are associated with ASO.…”
Section: Discussionmentioning
confidence: 99%